2022
DOI: 10.3390/pr10112180
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Recombinant Adeno-Associated Virus Production using Extended Kalman Filter

Abstract: The recombinant adeno-associated virus (rAAV) is a viral vector technology for gene therapy that is considered the safest and most effective way to repair single-gene abnormalities in non-dividing cells. However, improving the viral titer productivity in rAAV production remains challenging. The first step to this end is to effectively monitor the process state variables (cell density, GLC, GLN, LAC, AMM, and rAAV viral titer) to improve the control performance for an enhanced productivity. However, the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…However, until now, the failure case (biomanufacturing conditions) where JEKF fails as an unshared parameter estimator has not been formally reported. Recently, the JEKF was applied for monitoring rAAV production [ 19 ]. In developing this application, the authors dealt with a situation that resembles the failure case reported here.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…However, until now, the failure case (biomanufacturing conditions) where JEKF fails as an unshared parameter estimator has not been formally reported. Recently, the JEKF was applied for monitoring rAAV production [ 19 ]. In developing this application, the authors dealt with a situation that resembles the failure case reported here.…”
Section: Related Workmentioning
confidence: 99%
“… P and Q with uncorrelated elements. In case of the limited amount of data, it is very common to assume P and Q with uncorrelated elements in EKF applications [ 19 , 20 , 21 , 47 ]. This assumption means that the error covariance matrices P and Q are diagonal, with the diagonal elements being the noise variances (P and Q ) and off-diagonal elements equal to zero (P and Q ).…”
Section: Theoretical Analysismentioning
confidence: 99%
See 3 more Smart Citations